Sustaining Community-Scale Sanitation Services: Co-management by Local Government and Low-Income Communities in Indonesia - Willetts, Juliet; Mills, Freya; Al’Afghani, Mova (Frontiers in Environmental Science, 2020)
Ensuring sustainability of sanitation infrastructure assets and services over the long-term is crucial for achieving safe sanitation for all. Co-management is an emerging approach that balances state and citizen responsibility for services, with applicability to community-scale (or decentralised) sanitation systems in a city-wide context. In Indonesia more than 30,000 of these systems are typically managed solely by communities, however due to challenges in technical, social and financial aspects, commonly fall to disrepair. This paper presents qualitative research comprising document review, interviews and co-design workshops with local government and community management groups that developed a model for co-management of community-scale systems. The co-management model articulated four minimum responsibilities for local government: monitoring and corrective action; provision of technical and institutional support to community groups; formalisation of fee collection; and funding of large costs for rehabilitation and expansion. This model was developed and tested in two case study locations, and through this process, was deemed appropriate, acceptable and feasible for both local government and community management groups. Related changes to Indonesia’s national program guidelines were also identified to clearly articulate local government’s role. The agreed co-management approach aligns with the human right to sanitation by supporting local governments fulfil their legal mandate for services, promotes professionalised sustainable management arrangements, ensuring community-scale systems can contribute effectively to future citywide solutions.